2021
DOI: 10.1097/cce.0000000000000346
|View full text |Cite
|
Sign up to set email alerts
|

First and Second Waves of Coronavirus Disease 2019 in Madrid, Spain: Clinical Characteristics and Hematological Risk Factors Associated With Critical/Fatal Illness

Abstract: Objectives: This study aims to determine similarities and differences in clinical characteristics between the patients from two waves of severe acute respiratory syndrome coronavirus-2 infection at the time of hospital admission, as well as to identify risk biomarkers of coronavirus disease 2019 severity. Design: Retrospective observational study. Setting: A single tertiary-care center in Madrid. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 38 publications
5
20
1
Order By: Relevance
“…In contrast with most reports of second waves outside of South Africa, our study found that patients hospitalised during the second wave in a single hospital in the ECP were significantly older than in the first [6][7][8]. Of note, the second wave coincided with the end of the school and university years and also the annual summer public holidays in which there was significant liberalisation of lockdown rules.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast with most reports of second waves outside of South Africa, our study found that patients hospitalised during the second wave in a single hospital in the ECP were significantly older than in the first [6][7][8]. Of note, the second wave coincided with the end of the school and university years and also the annual summer public holidays in which there was significant liberalisation of lockdown rules.…”
Section: Discussioncontrasting
confidence: 99%
“…Until November 2020, there had been a shift towards patients that were younger, with fewer associated comorbidities and lower in-hospital mortality. The latter was probably multifactorial and linked to the younger age, the lower comorbidity burden, possibly better medical management and less severe disease [1,[6][7][8][9]. However, the B 1.1.7 variant that emerged in November 2020 in the south of England and spread to both Europe and the United States (US) has been associated with higher transmissibility and mortality [4-5-10].…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, most of these studies focused on a short follow-up period to outcome (28/30 days) [ García de Guadiana-Romualdo et al, 2021 ; Gregoriano et al, 2021 ]. Finally, differences in the predictive accuracies of biomarkers as D-dimer or IL-6 between the first and second wave have been reported, reflecting a different disease stage of patients on arrival to hospital [Mollinedo-Gajate et al, 2021] and a lower severity during the second wave [Fan et al, 2020] , conditions both affecting to the accuracy of biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been reports of at least two waves in numerous countries, including an initial one in the Spring of 2020 and a resurgence of cases in the Summer and Fall of 2020 [1][2][3][4][5][6][7][8][9][10]. A limited number of single-center studies have reported differences in laboratory values, demographic composition, and disease management between patients with COVID-19 admitted in the first and second waves [6,8,11,12]. Thus, there is substantial interest in comparing the clinical trajectories of patients with SARS-CoV-2 who were hospitalized across different waves of the pandemic to better understand the rapidly evolving epidemiology, pathophysiology, and health care dynamics of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%